2001
DOI: 10.1002/yea.760
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of 41 kb of the DNA sequence from the right arm of chromosome II of Schizosaccharomyces pombe

Abstract: We report the complete sequence of cosmid c18A7 (41 046 bp insert), located on the right arm of chromosome II of the Schizosaccharomyces pombe genome. The sequence, which partially overlaps with cosmids SPBC4F6 and SPBC336, contains 16 open reading frames (ORFs) capable of coding for proteins of at least 100 amino acid residues in length (one partial) and one small nucleolar RNA (snoRNA). Four known genes were found: swi10 (encoding a mating-type switching protein also involved in nucleotide excision repair); … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 34 publications
0
4
0
Order By: Relevance
“…Collectively, the results of our study have validated the findings of earlier reports that no single reference gene is stably expressed in all treatments [ 8 , 27 , 30 , 43 ]. The novel reference gene, DIMT , which encodes a dimethyladenosine transferase that, specifically dimethylates two adjacent adenosines and is situated within a conserved hairpin loop near the 3′-end of the 18S rRNA of the 40S ribosomal subunit[ 44 ], is differentially expressed among different developmental stages and sexes. The present study has also determined that RPII3 should be excluded as a stably expressed reference gene, similar to the findings of a previous study involving Raphanus sativus L.[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…Collectively, the results of our study have validated the findings of earlier reports that no single reference gene is stably expressed in all treatments [ 8 , 27 , 30 , 43 ]. The novel reference gene, DIMT , which encodes a dimethyladenosine transferase that, specifically dimethylates two adjacent adenosines and is situated within a conserved hairpin loop near the 3′-end of the 18S rRNA of the 40S ribosomal subunit[ 44 ], is differentially expressed among different developmental stages and sexes. The present study has also determined that RPII3 should be excluded as a stably expressed reference gene, similar to the findings of a previous study involving Raphanus sativus L.[ 45 ].…”
Section: Discussionmentioning
confidence: 99%
“…It is shown a high number of identical and conserved amino acids among the considered sequences of the ClpB from Escherichia coli (Gottesman et al, 1990), Synechococcus sp. (Eriksson and Clarke, 1996), Schizosaccharomyces pombe (Sanches et al, 2001) and Saccharomyces cerevisiae (Parsell et al, 1991). Of special note is the conservation of the ATPbinding motifs 1 and 2, which is typical of ClpB sequences.…”
Section: Comparison Of the P Brasiliensis Clpb And Related Sequencesmentioning
confidence: 99%
“…The sequences were: Escherichia coli (Gottesman et al, 1990), Synechococcus sp. (Eriksson and Clarke, 1996), Schizosaccharomyces pombe (Sanches et al, 2001) and Saccharomyces cerevisiae (Parsell et al,1991). Asterisks indicate amino acid identity and dots represent conserved substitutions.…”
Section: Expression Of the P Brasiliensis Clpbmentioning
confidence: 99%
“…Previous studies suggested that Sec6 is present in SPB and crucial for cytokinetic cell separation in S. pombe (490). An unexpected finding was Tpi1, which is a triosephosphate isomerase involving in various biosynthetic events (491). Other findings were more unexpected, including Cc736.03c, Psd3 and Cc1183.11.…”
Section: Resultsmentioning
confidence: 93%